Developing Standards for Language Teacher Education Programs in Indonesia: Professionalizing or Losing in Complexity? - Luciana Luciana (TEFLIN, 2004)
Setting standards for language teacher education programs, materials, and evaluation sparks some hope in attempts to improve the quality of the programs. Yet, this very fact augmented by my examination of ten language teacher education programs in Java, Bali, and Lampung (FKIP and PGRI) triggers a critical look at the idea of standard development. In particular, I would like to explore whether it can lead to a better professionalism or we are just lost in the complexity of the standardization itself. This paper consists of four sections. Departing from an overview of language teacher education programs in Indonesia and the theoretical foundations, some major problems in this area are identified. Following this, the discussion is focused on the idea of standard development for language teacher education programs in Indonesia. Eventually, some suggestions are put forth to highlight the need for establishing coherent curriculum framework bridging the two realms of language teacher education and school milieu as well as providing learners with knowledge base that enables them to cope with complex demands of school settings and more essentially, to act as an agent in the social change process.